Incidence of Cholera in Children under two years of age at the Dr. Soetomo Hospital, Surabaya - Haroen Noerasid; Pitono Soeparto; Bing Rudyanto; Moh. Sjaifullah Noer; Moh. Adnan (Paediatrica Indonesiana, 1975)
Stool cultures from 510 patients, admitted to the Children's Ward of the Dr. Soetomo Hospital with gastroenteritis, were examined. Fifty-six cases were found to have para Cholera El Tor (10.98%) and 56 patients showed positive E. coli (10.98%). The clinical features of para Cholera El Tor have been discussed, and compared with E. coli infections. We also reviewed the clinical observations of other writers. Clinically Cholera El Tor and E. coli have similar signs and symptoms. They differ only in: (a) Age (El Tor is usually found in older age groups). (b)Nutritional State (El Tor is found among the undernourished), (c) State of dehydration (El Tor causes dehydration more rapidly), and (d) Faeces (El Tor excretes more faeces per movement).